MEMBACA AL-JABIRI: MENGGALI INSPIRASI DARI POST-TRADISIONALISME ISLAM - A'isyah, Siti (LPPI Universitas Al-Qolam Malang, 2015)
Al-Jabiri’s thought, one of prominent thinkers of Islamic reform, considered as one with original ideas. His two main ideas, namely turats and hadatsah and epistemological critique of Islam (Arabic) is considered unique, despite the criticism leveled by some thinkers. The idea of turats and hadatsah emphasis on more comprehensive reading on turats accompanied by a more productive reading. His criticism on the epistemology of Islam (Arabic), which departed from the mapping of Arabic reason, is very popular; Bayani-Burhani-Irfani. These Al-Jabiri’s ideas, especially about turats and hadatsah, are inspiring this article. It can be used as a telescope to look at Pesantren tradition that became the basis of Al-Qolam tradition as well as its area of concern contained in its vision